2014
DOI: 10.1097/qai.0000000000000315
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Transportation Cost on Long-Term Retention in Clinic for HIV Patients in Rural Haiti

Abstract: Patients with transportation costs greater than $2 were 1.9 times more likely to be lost to care compared with those who paid less for transportation. HIV treatment programs in resource-constrained settings may need to pay closer attention to issues related to transportation cost to improve patient retention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
2
7
0
Order By: Relevance
“…Patient factors include limited time to attend clinic, low income, food insecurity, poor social support, and cultural norms [31][32][33]. Environmental factors include transport costs [34], lack of healthcare facilities close to patients, road conditions, seasonal weather, and political disruptions. Health system factors include negative experience at hospitals, medicine costs [35], and complex systems [36].…”
Section: Discussionmentioning
confidence: 99%
“…Patient factors include limited time to attend clinic, low income, food insecurity, poor social support, and cultural norms [31][32][33]. Environmental factors include transport costs [34], lack of healthcare facilities close to patients, road conditions, seasonal weather, and political disruptions. Health system factors include negative experience at hospitals, medicine costs [35], and complex systems [36].…”
Section: Discussionmentioning
confidence: 99%
“…Another significant finding is the association between rapid initiation of ART after HIV diagnosis and elevated risk of attrition. The absence of or inadequate pre-ART adherence counseling before enrollment may be the explanation [15]. However, a study conducted at the GHESKIO Centers in Haiti has shown higher retention among the same-day ART initiation group than the standard ART initiation group [28].…”
Section: Discussionmentioning
confidence: 99%
“…However, in Haiti, fewer than half of patients newly diagnosed with HIV who are eligible for ART initiate treatment within 2 years [ 3 ], and retention rates one year after initiating ART are below 80% [ 4 ]. These low retention rates are likely due to stigma, lack of understanding about HIV or ART, work and family commitments, long clinic wait times, and poverty, which makes high transportation costs to distant ART facilities a significant burden [ 5 ]. Further, inadequate staffing and few resources at health care facilities dedicated to improving retention in care contribute to these low rates.…”
Section: Introductionmentioning
confidence: 99%